Impact of a Web-Based Lifestyle Medicine Intervention: A Qualitative Study Among Rural Participants - Laurie Abbott; Jessica De Leon; Lucinda J. Graven (Nursing Reports, 2025)
Background: Chronic diseases negatively impact health outcomes and are attributed to elevated morbidity and mortality throughout the world. Rural populations are disproportionately affected by chronic diseases and have limited access to health programs and resources. The purpose of this qualitative study was to explore the cognitive impact that a web-based lifestyle medicine intervention had on participants recruited from rural community settings in the southeastern United States. This qualitative study was the second phase of a mixed methods design, which used a randomized controlled trial to evaluate intervention effects. Methods: The descriptive design of this qualitative study included semi-structured interviews to collect information about the impact of a lifestyle medicine intervention. The interviews were transcribed verbatim and analyzed using the grounded theory method of thematic analysis in an iterative process for discovering patterns, central themes, and concepts. Results: The four themes that emerged were (a) gaining awareness and overcoming barriers, (b) encouraging others as a “ripple effect”, (c) realizing actualities, and (d) seeing progress. These themes highlighted the cognitive impact of an online lifestyle medicine program and provided insights about how rural dwellers perceived and processed educational health information. Conclusions: This study shows that the intervention had a positive influence on participants that continued after participation. The findings of this study provide recommendations that can facilitate intervention development and implementation among rural populations.